2008
DOI: 10.1021/jp710172y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chirality on π-Stacking in Styrene and Maleimide Alternating Copolymers

Abstract: The effect of different chiral sequences in alternating copolymers of styrene and maleimide, poly(styrene-alt-dimethyl-N,N-propylamide) (SMI) was studied. The methods used for the SMI also applied to the general class of alternating copolymers of styrene and various maleimides. Only racemo-diisotactic polymers can associate into complexes because of the symmetrically distributed phenyl groups and maleimide monomers. This polymer is isotactic with respect to the chiral site of the styrene monomers (R, S) and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The design concept of our AP platform specifically referred to two previously reported properties of styrene-maleic anhydride/acid copolymers (SMAs): 1) the almost linear conformation at neutral pH that favors π-stacking and hydrophobic interactions of the styrene units and supports self-association as well as surface affinity (an effect caused by a stabilizing H-bond between the protonated carboxyl group and the neighboring, deprotonated carboxyl group of the diacid, [31,32] ) and 2) the fact that SMAs with a styrene to maleic acid ratio of 2:1 to 3:1 strongly interact with hydrophobic membrane proteins. [34,35] Accordingly, we selected the 10-30, 80-30, and 120-30 backbone types with an optimal styrene to MA ratio of 2.3:1 and PEGylated the SMAs upon reaction of the anhydride with an amine terminated PEG to introduce a stable amide bond. [36] By selecting a P EG /S-ratio ≥ 8 we could avoid self-association (see Figure 1A) while providing a rather pH-independent solubility (data not shown) and linear conformation stabilized by hydrogen bond formation between the remaining, over a large pH range (pH > 3.5) deprotonated carboxylic acid group, and the NH-group of the amide bond.…”
Section: Resultsmentioning
confidence: 99%
“…The design concept of our AP platform specifically referred to two previously reported properties of styrene-maleic anhydride/acid copolymers (SMAs): 1) the almost linear conformation at neutral pH that favors π-stacking and hydrophobic interactions of the styrene units and supports self-association as well as surface affinity (an effect caused by a stabilizing H-bond between the protonated carboxyl group and the neighboring, deprotonated carboxyl group of the diacid, [31,32] ) and 2) the fact that SMAs with a styrene to maleic acid ratio of 2:1 to 3:1 strongly interact with hydrophobic membrane proteins. [34,35] Accordingly, we selected the 10-30, 80-30, and 120-30 backbone types with an optimal styrene to MA ratio of 2.3:1 and PEGylated the SMAs upon reaction of the anhydride with an amine terminated PEG to introduce a stable amide bond. [36] By selecting a P EG /S-ratio ≥ 8 we could avoid self-association (see Figure 1A) while providing a rather pH-independent solubility (data not shown) and linear conformation stabilized by hydrogen bond formation between the remaining, over a large pH range (pH > 3.5) deprotonated carboxylic acid group, and the NH-group of the amide bond.…”
Section: Resultsmentioning
confidence: 99%
“…Dimethyl-N, N-propylamide imidized SMAh was found to self-assemble to nanotubes, which were said to arise from the π-stacking of the styrenes and the van der Waals interactions between the maleimide units [122]. Theoretical studies showed that only racemo-diisotactic configuration of imidized SMAh polymer could form complexes by π-stacking, when the phenyl groups and maleimides are symetrically distributed [123].…”
Section: Methodsmentioning
confidence: 99%
“…31 Figure 1 (bottom) shows the 1 H NMR spectrum of the PIB-alt-MAH copolymer with long PIB tails; the peaks associated with the vinyl ether end group have disappeared and the aromatic peaks have coalesced into a large multiplet at 7.32-7.11 ppm (d and e), possibly due to π-π stacking of adjacent phenyl rings. 32 This phenomenon is also manifested in a significant downfield chemical shift of the ultimate methylene group of the PIB tail (c).…”
Section: Synthesis and Characterization Of Pib-alt-mah Copolymersmentioning
confidence: 99%